Materiais e técnicas para nanoestruturas magnetoelétricas compósitas - Mori, Thiago José de Almeida (2014)
Hybrid nanostructures which integrate two or more technologically interesting physical properties are fundamental for developing new generations of electronic devices. Exhibiting at least two coupled ferroic orders, multiferroics are an outstanding class of multifunctional materials. Compounds which present coupling between ferromagnetism and ferroelectricity are specially interesting. Although natural multiferroics are rarely found, the possibility of obtaining strain-mediated magnetoelectric coupling in composite structures, by integrating magnetostrictive and piezoelectric layers, paves the way to control electric properties by applying magnetic field or to the electric control of magnetism. Nevertheless, most scientific efforts have been on monophasic compounds or bulk composites. Considering the incorporation of magnetoelectric nanostructures in devices, expanding the scope of the magnetoelectric effect and targetting it to different kinds of applications is needed. Besides new characterization techniques, seeking new alternative materials to the lead-based piezoelectrics or oxide-based magnetostrictives is necessary. Recently, a few works using semiconductors such as ZnO and AlN, or amorphous magnetic alloys such as those based on Co, Fe and Ni, have been reported. In spite of not presenting remarkable piezoelectric and magnetostrictive effects, the features of such materials are promising for high frequency applications, for instance. Considering these issues, four independent surveys are presented. Firstly, the origin of the coupling, latest advances and current scenario of the field are reviewed. Then magnetostriction measurements in thin films are addressed by employing a direct technique based on the cantilever-capacitance method. The goals are to study magnetoelastic properties of some materials whose magnetostriction are not found very often in literature, and to check the reliability of this technique for investigating thin films. In this sense, measurements of some amorphous magnetic alloys mainly based on Co, Fe and Ni are performed. Most samples presents larger magnetoelastic response for magnetic field applied along the magnetization easy axis, as opposed to the theoretically expected. Two investigations on aluminum nitride thin films are reported. Firstly, the growth of AlN films onto several different substrates and buffer layers is studied. Films grown onto glass and polyimide show excellent structural properties for eletromechanical systems and flexible electronics applications. Samples with low residual stress on silicon substrates, suitable for incorporating in existing technologies, are obtained. Secondly, bilayers composed by AlN and ferromagnetic films are investigated. In addition to the structural and morphological properties of the AlN films which are checked, the magnetic characterization of the structures also contributes to design multilayers for exploring the magnetoelectric effect. Finally, problems involving electric fields in scanning probe microscopies are adressed. Surface images of AlN piezoelectric films are systematically acquired. Among other major observations, the possibility of getting reliable piezoresponse images of strongly polarized areas as well as of visualizing ferroelastic domains, is demonstrated. Furthermore, a new microscopy for investigating a sample s ferro and piezoelectric properties is proposed, exploring the direct piezoelectric effect. By utilizing acoustic excitation and electrical detection, the potency of this technique is illustrated with measurements on quartz and AlN surfaces.